2015
DOI: 10.3346/jkms.2015.30.11.1667
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Resilience in Attenuating Emotional Distress and Aggression Associated with Early-life Stress in Young Enlisted Military Service Candidates

Abstract: Early life stress (ELS) may induce long-lasting psychological complications in adulthood. The protective role of resilience against the development of psychopathology is also important. The purpose of this study was to investigate the relationships among ELS, resilience, depression, anxiety, and aggression in young adults. Four hundred sixty-one army inductees gave written informed consent and participated in this study. We assessed psychopathology using the Korea Military Personality Test, ELS using the Child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
(30 reference statements)
1
15
0
Order By: Relevance
“…In fact, the results suggest that individuals who are low in resilience may be especially at-risk for depressed and anxious mood as well as sleep impairments. The protective role of resilience against negative affect has been addressed in many studies [56][57][58], and resilience interventions have shown their effectiveness in reducing stress, depression, and anxiety [59,60]. Given our finding that negative moods predict poorer sleep quality, combined with research documenting a relationship between sleep quality and immune functioning [61], protecting individuals from elevated negative moods may be particularly important during a pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, the results suggest that individuals who are low in resilience may be especially at-risk for depressed and anxious mood as well as sleep impairments. The protective role of resilience against negative affect has been addressed in many studies [56][57][58], and resilience interventions have shown their effectiveness in reducing stress, depression, and anxiety [59,60]. Given our finding that negative moods predict poorer sleep quality, combined with research documenting a relationship between sleep quality and immune functioning [61], protecting individuals from elevated negative moods may be particularly important during a pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike previous trials (e.g. [ 72 , 73 ]), we covered the entire age range from 14 to 92 years. As emphasized in the review of Johnson et al [ 66 ], an expansion of the range of populations investigated is necessary to detect buffering factors due to the requirements of statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…Negative psychosocial experiences in early life increase an individual's intrinsic vulnerability to psychiatric problems, as shown in a large prospective study of a US military cohort (Smith et al, ). Resilient people recover their normal function and regulate their emotions when responding to traumatic events in adulthood, using psychosocial resilience and cognitive flex­ibility (Gates et al, ; Kim et al, ). However, military service members who experienced severe childhood maltreatment are mentally and physically vulnerable during military training and service tasks (Van Voorhees et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this high stress, there is little empirical evidence from Korea to support that resilience mediates trauma and psychopathology later in life. Nonetheless, limited data support that Korean military service candidates’ resilience buffers the impact of early life stress on emotional distress and military adjustment (Choi et al, ; Kim et al, ).…”
Section: Stressful Military Service In Republic Of Korea Marinesmentioning
confidence: 99%
See 1 more Smart Citation